2020
DOI: 10.33899/rden.2020.127159.1033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Casein Phosphopeptide–Amorphous Calcium Phosphate Mousse versus Natural Raw Fresh Milk on Enamel Surface Roughness After a pH Challenge

Abstract: Aims: The aim of this study is to evaluate the effect of CPP−ACP, raw, fresh buffalo milk and cow milk on surface roughness of artificial initial caries lesions. Materials and Methods: 100 sound maxillary first premolar extracted for the purpose of orthodontic treatment had been collected and randomly divided into four groups, in all groups the teeth subjected to pH cycle procedure then treated with: Group1: n(25) deionized water, group2: n(25) CPP−ACP tooth mousse, group3: n(25) raw cow milk, group4: n(25) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
2
1
Order By: Relevance
“…A recent study by Al-Ani and Al-Naimi concluded that CCP-ACP tooth mousse, raw fresh buffalo, and cow milk were all effective remineralizing agents, reducing the enamel surface roughness after a pH challenge. 33 They however, in contrast to our findings, stated that CCP–ACP tooth mousse showed more superior results.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study by Al-Ani and Al-Naimi concluded that CCP-ACP tooth mousse, raw fresh buffalo, and cow milk were all effective remineralizing agents, reducing the enamel surface roughness after a pH challenge. 33 They however, in contrast to our findings, stated that CCP–ACP tooth mousse showed more superior results.…”
Section: Discussioncontrasting
confidence: 99%
“…This could be due to their nature that enables calcium and phosphate ions to be released from the remineralizing agent to infiltrate and diffuse surface and subsurface enamel porosities, 25 reduce the lesion depth, improve surface roughness and promote enamel remineralization. 26 These results agree with Al-Ani et al, 28 who concluded that CPP−ACP tooth mousse improved roughness significantly after pH cycling of enamel. Specimens treated with nanohydroxyapatite (Nano P) has a smother surface than CPP-ACFP.…”
Section: Discussionsupporting
confidence: 86%
“…The solution of demineralization contains “0.075 mM/L acetic acid, 1 mM/L calcium chloride, and 2 mM/L potassium phosphate” and the pH will be adjusted to 4.3. Whereas the solution of remineralization, which contains “150 mM/L potassium chloride, 1.5 mM/L calcium nitrate, and 0.9 mM/L potassium phosphate” and the pH will be adjusted to 7 [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…To simulate acidic challenge in a daily manner inside the environment of the mouth, crown samples were soaked in a demineralization solution for six hours, then were rinsed with distilled water for (1 minute) and then immersed in the prepared remineralizing agent for 17 hours. These steps were repeated once per day for 10 days [ 10 ]. The demineralizing and remineralizing solutions were refreshed daily.…”
Section: Methodsmentioning
confidence: 99%